Entre abundância e insegurança alimentar: soja e processos de globalização - Calado, Virgínia Henriques (Trabalhos de Antropologia e Etnologia, 2020)
In this paper we analyze the circulation and appropriation of a food product – soya and its derivatives – in different geographic contexts and in scenarios that oppose food abundance and scarcity. On the one hand, we will pay attention to the flows of this commodity from the macrobiotics proposal, and, on the other, we will observe its introduction in Mozambique as a cash crop. Thus, we will consider soya transits from a food proposal integrated into a worldview and, on another level, as an expanding agricultural crop, presented as a way to reduce poverty and food insecurity. For the analysis of these aspects we will take into account the discussion about whether or not global material flows constitute global cultural flows. We will seek soya in articulation with dimensions such as globalization, territory and acceptability.